RANCANG BANGUN SISTEM PENGUKURAN TINGGI TANAMAN SAYUR DAN SISTEM MONITORING PERTUMBUHAN TANAMAN MENGGUNAKAN METODE REGRESI POLINOMIAL - Fadhlurrahman, Adam Farrel; Nurussa’adah, n/a; Siwindarto, Ponco (Jurnal Mahasiswa TEUB, 2024)
Plant height is an important indicator to show the performance of the media or agricultural land. Therefore, this research aims to realize an effective and efficient plant height measurement system for lettuce vegetable cultivation using ultrasonic sensors, and realize a growth monitoring system. The sensor measurement data is processed using the polynomial regression method to determine the plant growth graph. Ultrasonic sensor testing for plant height measurement shows the largest error value that occurs is 0.045%. The monitoring system test results show that all sensor data can be displayed on the TFT display and the measurement results are successfully stored in the Micro SD Card. Overall, the lettuce plant height measurement system using two ultrasonic sensors shows the results of the regression equation y = 0.0025x2 + 0.4976x - 1.5397 and y = -0.002x2 + 0.6246x - 2.4707. The polynomial regression equation is used to generate growth notifications displayed on the TFT display. With this system, it is expected to facilitate farmers in monitoring plant growth and decision making. Keywords— Plant Height Measurement, Monitoring System, Ultrasonic Sensor, Polynomial Regression.